Does economic diversification impact on the relationship between policies and volatility? - Moore, Winston (Central Bank of Barbados [St. Michael]BB, 2007)
Attempts to evaluate the relationship between diversification, policies and economic volatility for a sample of 147 countries for the perid 1970 to 2005.